Nalar Hukum Islam Terhadap Konsep Perpajakan Modern - Murtadho, Ali (IAIN Palangka Raya, 2017)
Tax discourse in the context of the modern state will always be attractive along with the shifting orientation, purpose and function of the state that not only maintains public order and public security -nachwakersstaat - but the state must be able to present a prosperous condition -verzogingstaat or welvarsstaat- in the midst of its people. This gives consequences to the state in taking responsibility for the welfare of its people. Tax is one of the instruments used by the state as capital to carry out the welfare mission levied from the people, on the people's mandate as well as taxes are then distributed. The construction of thought in this peaper is based on the benefit aspect of the function and role of the tax.